Factors Affecting the Outcome of the Operable Subtype Luminal B Breast Cancer Treatment - Meri Novita; Wisma Arif Harahap; Rahmat Taufik (International Journal Labs, 2022)
Breast cancer is a condition of uncontrolled breast cell proliferation that most frequently develops from the ductal epithelial cells (85%) or lobules (15%) of the breast glands. Poor prognoses for patients can result from cancer's extensive organ metastasis, now the second largest cause of cancer death in women. This study aims to identify the variables that affect how well patients with the operable breast cancer subtype Luminal B respond to treatment at RSUP DR M Djamil Padang. This research used a cross-sectional methodology with a retrospective study approach to identify characteristics that affect the treatment outcome for operable breast cancer subtype luminal B at RSUP DR. M. Djamil Padang. From August to November 2022, the study was carried out in the Oncology Surgery Division of RSUP DR. M. Djamil Padang. With HER2 being the main component, multivariate analysis revealed that HER2 and the kind of therapy were significantly connected with the treatment outcome for cancer patients.